If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4w + 3 = (7w + -6)(7w + -6) Reorder the terms: 3 + 4w = (7w + -6)(7w + -6) Reorder the terms: 3 + 4w = (-6 + 7w)(7w + -6) Reorder the terms: 3 + 4w = (-6 + 7w)(-6 + 7w) Multiply (-6 + 7w) * (-6 + 7w) 3 + 4w = (-6(-6 + 7w) + 7w * (-6 + 7w)) 3 + 4w = ((-6 * -6 + 7w * -6) + 7w * (-6 + 7w)) 3 + 4w = ((36 + -42w) + 7w * (-6 + 7w)) 3 + 4w = (36 + -42w + (-6 * 7w + 7w * 7w)) 3 + 4w = (36 + -42w + (-42w + 49w2)) Combine like terms: -42w + -42w = -84w 3 + 4w = (36 + -84w + 49w2) Solving 3 + 4w = 36 + -84w + 49w2 Solving for variable 'w'. Reorder the terms: 3 + -36 + 4w + 84w + -49w2 = 36 + -84w + 49w2 + -36 + 84w + -49w2 Combine like terms: 3 + -36 = -33 -33 + 4w + 84w + -49w2 = 36 + -84w + 49w2 + -36 + 84w + -49w2 Combine like terms: 4w + 84w = 88w -33 + 88w + -49w2 = 36 + -84w + 49w2 + -36 + 84w + -49w2 Reorder the terms: -33 + 88w + -49w2 = 36 + -36 + -84w + 84w + 49w2 + -49w2 Combine like terms: 36 + -36 = 0 -33 + 88w + -49w2 = 0 + -84w + 84w + 49w2 + -49w2 -33 + 88w + -49w2 = -84w + 84w + 49w2 + -49w2 Combine like terms: -84w + 84w = 0 -33 + 88w + -49w2 = 0 + 49w2 + -49w2 -33 + 88w + -49w2 = 49w2 + -49w2 Combine like terms: 49w2 + -49w2 = 0 -33 + 88w + -49w2 = 0 Begin completing the square. Divide all terms by -49 the coefficient of the squared term: Divide each side by '-49'. 0.6734693878 + -1.795918367w + w2 = 0 Move the constant term to the right: Add '-0.6734693878' to each side of the equation. 0.6734693878 + -1.795918367w + -0.6734693878 + w2 = 0 + -0.6734693878 Reorder the terms: 0.6734693878 + -0.6734693878 + -1.795918367w + w2 = 0 + -0.6734693878 Combine like terms: 0.6734693878 + -0.6734693878 = 0.0000000000 0.0000000000 + -1.795918367w + w2 = 0 + -0.6734693878 -1.795918367w + w2 = 0 + -0.6734693878 Combine like terms: 0 + -0.6734693878 = -0.6734693878 -1.795918367w + w2 = -0.6734693878 The w term is -1.795918367w. Take half its coefficient (-0.8979591835). Square it (0.8063306952) and add it to both sides. Add '0.8063306952' to each side of the equation. -1.795918367w + 0.8063306952 + w2 = -0.6734693878 + 0.8063306952 Reorder the terms: 0.8063306952 + -1.795918367w + w2 = -0.6734693878 + 0.8063306952 Combine like terms: -0.6734693878 + 0.8063306952 = 0.1328613074 0.8063306952 + -1.795918367w + w2 = 0.1328613074 Factor a perfect square on the left side: (w + -0.8979591835)(w + -0.8979591835) = 0.1328613074 Calculate the square root of the right side: 0.36450145 Break this problem into two subproblems by setting (w + -0.8979591835) equal to 0.36450145 and -0.36450145.Subproblem 1
w + -0.8979591835 = 0.36450145 Simplifying w + -0.8979591835 = 0.36450145 Reorder the terms: -0.8979591835 + w = 0.36450145 Solving -0.8979591835 + w = 0.36450145 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '0.8979591835' to each side of the equation. -0.8979591835 + 0.8979591835 + w = 0.36450145 + 0.8979591835 Combine like terms: -0.8979591835 + 0.8979591835 = 0.0000000000 0.0000000000 + w = 0.36450145 + 0.8979591835 w = 0.36450145 + 0.8979591835 Combine like terms: 0.36450145 + 0.8979591835 = 1.2624606335 w = 1.2624606335 Simplifying w = 1.2624606335Subproblem 2
w + -0.8979591835 = -0.36450145 Simplifying w + -0.8979591835 = -0.36450145 Reorder the terms: -0.8979591835 + w = -0.36450145 Solving -0.8979591835 + w = -0.36450145 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '0.8979591835' to each side of the equation. -0.8979591835 + 0.8979591835 + w = -0.36450145 + 0.8979591835 Combine like terms: -0.8979591835 + 0.8979591835 = 0.0000000000 0.0000000000 + w = -0.36450145 + 0.8979591835 w = -0.36450145 + 0.8979591835 Combine like terms: -0.36450145 + 0.8979591835 = 0.5334577335 w = 0.5334577335 Simplifying w = 0.5334577335Solution
The solution to the problem is based on the solutions from the subproblems. w = {1.2624606335, 0.5334577335}
| 12=7c-9 | | 6x^2-47x-46=0 | | 7x+7[x-5]=-147 | | -5(1-5x)+5(-8x-2)=-4x-8x+3 | | 13y+5=5y-5 | | 2(x-4)=4(x-2) | | X-(-2)=6 | | 5(x+3)=3(2x-1) | | 1a+2=(-9) | | -4x-5[-x+10]=-43 | | 6x-8(x+3)=-14 | | 8x+7x-6x=18 | | i=400*0.0013*2 | | -6x+4[-2x+8]=130 | | x^2+39x+47=0 | | -2+8=5-(10p+4) | | i=400*0.13*2 | | 2x+6[-5x-15]=190 | | 4-3x+8=5x-4 | | 70x^2-53x+9=0 | | 2(x+4)=x-7 | | 26x-14=3 | | -10+3m=2(4m+-5) | | X+50=210 | | 7x+6[-x-17]=-109 | | x+x+(x-45)+(x-45)+(x-45)=540 | | x=28.75+0.25y | | 2(x-1)+x=4+5 | | x=320+.2x | | 4x-y+65=180 | | 4(x+4)=x-7 | | 3x-7[2x+6]=90 |